2017
DOI: 10.1099/jmm.0.000395
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ISAba1 in association with a novel allelic variant of the β-lactamase ADC-82 and class D β-lactamase genes mediating carbapenem resistance among the clinical isolates of MDR A. baumannii

Abstract: High incidence of IC-II clones, novel resistance determinants (ADC-82) and elevated resistance mediated by ISAba1 reported here will be of enormous importance while assessing the emergence of extremely resistant A. baumannii in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…An earlier study showed CC108 as the predominant clone in India27, while Saranathan et al 23 reported CC103 and CC92 as the prevalent clonal complexes in south India. The same investigators also observed the predominance of clonal complexes CC92 followed by CC44726. Although in the current study, none of the isolates belonged to CC92, it was found to be the subgroup founder of CC208.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…An earlier study showed CC108 as the predominant clone in India27, while Saranathan et al 23 reported CC103 and CC92 as the prevalent clonal complexes in south India. The same investigators also observed the predominance of clonal complexes CC92 followed by CC44726. Although in the current study, none of the isolates belonged to CC92, it was found to be the subgroup founder of CC208.…”
Section: Discussionsupporting
confidence: 65%
“…Among ESBLs, bla PER-like was the most common and identified across all the four centres whereas other studies showed 54 and 81 per cent of bla PER-like , respectively2226. bla TEM-1 was found only among AIIMS, CMC and PGIMER isolates.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…ADC-82 is a recently discovered allelic variant that is resistant to a wide spectrum of cephalosporins 39. In MDR-CQD, there was a T to C point mutation at position 731 in the ADC-82 gene, corresponding to amino acid change L244P, which might have resulted in increased expression.…”
Section: Resultsmentioning
confidence: 99%
“…A. baumannii has high intrinsic resistance to several antibiotics and a tendency to acquire resistance genes that rise its antimicrobial resistance patterns [ 4 ]. Permeability defects, synthesis of numerous β -lactamases (extended-spectrum β -lactamase (ESBL), oxacillinase (OXA), and metallo- β -lactamase (MBL) types), overexpression of intrinsic β -lactamases, and efflux pumps are found to be major resistance mechanisms exhibited by A. baumannii [ 5 ]. Most A. baumannii strains have become progressively resistant to nearly all antibiotics that are currently available due to the existence of mobile genetic elements, such as plasmids and insertion sequences [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%